2017
DOI: 10.1016/j.foreco.2017.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the spatial and temporal dynamics of species interactions in Fagus sylvatica and Pinus sylvestris forests across Europe

Abstract: The productivity and functioning of mixed-species forests often differs from that of monocultures. However, the magnitude and direction of these differences are difficult to predict because species interactions can be modified by many potentially interacting climatic and edaphic conditions, stand structure and previous management. Process-based forest growth models could potentially be used to disentangle the effects of these factors and thereby improve our understanding of mixed forest functioning while facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 69 publications
(75 reference statements)
1
18
0
Order By: Relevance
“…According to the estimates of our mixed model, the strongest effect, which explained most of the growth variation, was actually derived from the variation in DBH among trees and sites (note that size differences in our study are mainly due to age differences and not due to differences in canopy status). Our finding that mixing benefits increased with tree size in beech is in agreement with results of two recent studies, which reported increasing mixing benefits for beech with tree size/stand age in combination with spruce (Houpert et al, 2018) and pine (Forrester et al, 2017).…”
Section: Mixing Benefits For Both Species Increase With Tree Size Andsupporting
confidence: 93%
“…According to the estimates of our mixed model, the strongest effect, which explained most of the growth variation, was actually derived from the variation in DBH among trees and sites (note that size differences in our study are mainly due to age differences and not due to differences in canopy status). Our finding that mixing benefits increased with tree size in beech is in agreement with results of two recent studies, which reported increasing mixing benefits for beech with tree size/stand age in combination with spruce (Houpert et al, 2018) and pine (Forrester et al, 2017).…”
Section: Mixing Benefits For Both Species Increase With Tree Size Andsupporting
confidence: 93%
“…According to Forrester et al (2017), for example, mixed and unmixed stands can vary considerably in the productivity, function, and stability, the extent and direction of these differences being very heterogeneous. In the context of higher structural diversity, correlation with the production of above-ground biomass has been confirmed for the pine stands (Balvanera et al, 2006;Szwagrzyk & Gazda, 2007;Ercanli & Kahriman, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…At very young development stages, the growth of European beech suffered from the mixture but at medium and old development stages, European beech benefitted from the mixture. Similarly, the mixing effect for European beech with Pinus sylvestris (L.) was predicted to increase with stand age as the early dominance of Pinus sylvestris, in terms of height, was lost [56]. The mixture therefore not only affects the productivity of the mixed stands but also the temporal dynamics of the tree species interactions [19].…”
Section: Mixing Effects In Norway Spruce-european Beech Standsmentioning
confidence: 99%